Croatia - Country Economic Memorandum : A Strategy for Growth through European Integration, Volume 2. Main Report - World Bank (Washington, DC, 2013)
For Croatia, the challenge is to create conditions that will attract investment and produce growth. These conditions can broadly be categorized as (a) stable, progressive and predictable laws and institutions; (b) efficient labor and financial markets; (c) macroeconomic and financial stability; (d) social and environmental sustainability; (e) effective integration into the European infrastructure networks ensuring competitive cost and quality; and (f) a dynamic business-oriented environment which facilitates the production of high value added goods and promotes the adoption of efficient processes and innovative technologies. This Report proposes a reform strategy for faster economic growth through European integration. Other key inputs for creating a favorable investment climate and consolidating growth prospects include skilled labor, efficient financial markets, and high-quality cost-efficient infrastructure services. Croatia has already achieved substantial progress in these areas. However, pursuing reforms in these sectors would not be costly and would be good for growth and European integration. Thus, higher education reform should be pursued, as should reforms to create market-oriented infrastructure institutions as envisaged in EU Directives, including the institutional development of regulators and the strengthening of the competition agency. The highly competitive European environment requires, in particular, well-focused training and higher education programs that offer firms qualified staff and adequate skills for an innovation-driven knowledge economy. The further deepening of financial markets, which is closely connected to the reforms in the legal and institutional framework outlined above, ought to focus also on the strengthening of the regulatory and supervisory functions, particularly in the non-banking sectors. Similarly, market-oriented energy, transport, and communications are crucial to enhance the global competitiveness of the Croatian economy and to foster its integration into the European economy while creating opportunities for FDI.